Use of reverse transcription-polymerase chain reaction (RT-PCR) for Cymbidium mosaic virus (CyMV) detection in orchids - Mat, Mazidah (2000)
The reverse transcription-polymerase chain reaction CRT-PCR) was adapted for detection of Cymbidium mosaic virus CCyMV) in orchids. The oligonucleotide primers used were selected from the predicted homologous coat protein region of CyMV and other Potexviruses which enabled to amplify approximately 313 bp and 227 bp fragments using optimum reaction conditions of 2.5 mM MgCh and 30 cycles of amplification. The RT-PCR allowed the detection of CyMV RNA and virion in purified fonns as well as in crude tissue extracts of orchid. Direct CyMV RNA detection was possible in leaves, shoots, stems, roots and petals. The detection limits of RNA in purified CyMV and virion by RT-PCR described were 10 ng and 2 ng, respectively. The PCR amplified fragments were confinned to be CyMV-specific by dotblot hybridization with DIG-labelled CyMV cDNA probe. The suitability of the RT-PCR in routine testing of CyMV was detennined and compared with those of DAS-ELISA. Thirty samples of leaf tissues representing various genera or hybrids of cultivated local orchid from glasshouse and commercial nurseries were tested for CyMV by RT-PCR and DAS-ELISA. Among 15 samples that tested positive for CyMV infection by DAS-ELISA, only 7 samples gave the expected amplification fragments when subjected in RTPCR assays. The equal detection limit on purified CyMV virion by RT-PCR and DAS-ELISA and lower sensitivity of RT-PCR in detecting CyMV in a field indexing trial suggested that RT-PCR is unsuitable to replace DAS-ELISA for routine testing of CyMV in local orchids.